Multidrug-resistant Escherichia coli O157 contamination of beef and chicken in municipal abattoirs of Southwest Nigeria (2012)
Indiscriminate antibiotics usage in food animals and unhygienic meat processing could predispose meat consumers to risks of antibiotic resistant bacterial contamination and infection. This study investigated thè contamination of meat ffom cattle and chicken slaughtered for human consumption with E. coli 0157:H7 at thè metropolitan abattoirs and slaughtered slabs of selected poultry farms in Lagos and Ibadan, Nigeria. The aim was to compare thè prevalence and antibiotic susceptibility pattems across thè different locations and climatic seasons. The organism was isolated by cultural method using selective media and confirmed serologically using latex agglutination kits (OxoidR IJK). Antibiotic susceptibility to ten antimicrobial agents was performed by disc diffiision method using commercial Grana negative discs. Out of 800 meat samples collected, thè overall prevalence of 17.1% (comprising of 19.8% and 14.5% of beef and chicken respectively) was obtained. The prevalence of E. coli 0157:H7 in beef ffom Ibadan and Lagos were 28.5% and 11.0%, while those of chicken from Ibadan and Lagos markets were 13.0% and 14.0%, and ffom Ibadan and Lagos farms were 18.0% and 13.0% respectively. The prevalence of E. coli 0157 was significantly higher in beef compared to chicken (p<0.05), while during wet season, contamination of beef was also higher than in dry and significantly higher in beef from Ibadan than Lagos abattoir. All thè isolates were resistant to one or multiple antibiotics, but thè highest resistance of 91.1 % was to tetracycline and nine different resistance pattems were observed among thè isolates. Indiscriminate antibiotics usage in livestock predisposes meat consumers to risks of antibiotic resistant Escherichia coli 0157:H7 in Southwest Nigeria. Regulatory control of antibiotics usage in livestock production, meat hygiene and pharmaco-epidemiological surveillance in food animals is hereby recommended to ensure consumer safety